Mexico : Report on the Observance of Standards and Codes (ROSC)-Data Module Volume I. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Report on the Observance of Standards and Codes-Data Module for Mexico. Despite the progress made and envisaged, there is scope for further improvement. The IMF staff mission identified the need for greater consistency in data recording across agencies and for regular inter-institution reconciliation exercises to resolve data discrepancies. One source of discrepancies is fixed capital formation of state and local governments, which-given the weight that these subnational units have in the aggregate-may well contribute to the significant divergence between measures of investment in the government finance statistics and in the national accounts. Accuracy and reliability of national accounts data are generally adequate and have improved since 2010.